Characteristics of Two Kota Soil Series - Bhola, S. N.; Singh, Gurmei.; Dayal, Rajbans (Indian Forester, 1969)
On the basis of physical and chemical characteristics and morphological features of different soil profiles studied in different parts of the region, the soils of Kota have been classified into two different series, namely Kota clay (Dark Gray Brown) and Kota Clay loam (Brown). Out of eighty five profiles studied in different parts of the region, the two representing the two soil series established have been described. The clay content and the fertility status in case of Kota Clay series is higher as compared to that of Kota Clay loam series. The physical constants and different ratio like erosion ratio, dispersion ratio, etc., show that Kota clay soils are nearly non-erosive but for their property of cracking and are poorly drained, while Kota clay loam soils are more erosive in nature and are moderately well drained. The buffering curve reveals that the Kota clay soils have 3.5 times higher buffering capacity as compared to that of Kota clay loam ones.